The Role of NT-proBNP Levels in the Diagnosis of Hypertensive Heart Disease - Angeliki Mouzarou; Nikoleta Hadjigeorgiou; Despo Melanarkiti; Theodora Eleni Plakomyti (Diagnostics)
Hypertension is a major risk factor of various cardiac complications, including hypertensive heart disease (HHD). This condition can lead to a number of structural and functional changes in the heart, such as left ventricular hypertrophy, diastolic dysfunction, and, eventually, systolic dysfunction. In the management of hypertensive heart disease, early diagnosis and appropriate treatment are crucial for preventing the progression to congestive heart failure. One potential diagnostic marker that has gained attention in recent years is the N-terminal pro-brain natriuretic peptide (NT-proBNP). The natriuretic peptides, including the brain natriuretic peptide (BNP) and its inactive N-terminal fragment, are secreted by the myocardium in response to increased wall stress and volume overload. In patients with hypertensive heart disease, increased NT-proBNP levels may reflect the structural and functional changes occurring in the myocardium as a result of chronic pressure overload. Several studies have investigated the diagnostic utility of NT-proBNP in hypertensive heart disease. NT-proBNP levels can be a useful adjunct in the diagnosis of hypertensive heart disease, particularly in the assessment of diastolic dysfunction and left ventricular hypertrophy. This review paper explores the role of NT-proBNP levels in the diagnosis of hypertensive heart disease.